Utility of pap smears and mammograms in midlife urban Malaysian women - Adeeb N,; Nur-Azurah AG,; Ong FB,; Seri SS,; Shamsuddin K,; Noor-Aini MY,; Sharifah NA,; Zahiah M, (Penerbit UKM, 2008)
Cancers of the breast and cervix made up 30.4% and 12% of all cancer cases in Malaysia. Thus screening for reproductive organ cancers as women approached menopause becomes exceedingly important. The study reports the baseline assessment tests of 495 disease free urban Malaysian women aged 45 years and above who volunteered in a healthy lifestyle intervention study. The sample comprised of 58.0% premenopaused and 42.0% postmenopaused women with an average age of 51.27±5.35 years old. Over two thirds were Chinese followed by Malays and Indians. Overall, abnormal Pap smears were seen in 7.6% comprising of 1.3% cervical intraepithelial neoplasia (CIN), 6.1% human papilloma virus (HPV) infection and 0.2% atypical squmous cells of undetermined significances (ASCUS). Yeast and other infections were found in 6.9% and 1.9% respectively. Comparatively, postmenopausal women had a 2.8 fold higher cancerous changes whereas premenopausal women had a higher infection rate, 11.8% vs. 4.7% respectively (p=0.024) with comparable HPV infection rates in both. This study found 1.3% had breast cancer (BC) with 3.6% requiring a biopsy while 3.4% needed regular follow up. Postmenopaused women had more abnormal mammograms (p<0.0005) of a graver nature, requiring monitoring although the rate of BC was lower than the premenopaused, 0.010 versus 0.015. The findings identified better vigorous screening for malignant carcinoma of the cervix in postmenopausal women as the incidence was higher. As for breast abnormalities, screening should begin at an earlier age, amongst pre- and postmenopausal women from 45 years old and above